Progress in Cryptology - INDOCRYPT 2009 10th International Conference on Cryptology in India, New Delhi, India, December 13-16, 2009, Proceedings - Roy, Bimal Kumar; Sendrier, Nicolas (Security and Cryptology ;, 2009)
This book constitutes the refereed proceedings of the 10th International Conference on Cryptology in India, INDOCRYPT 2009, held in New Dehli, India, in December 2009. The 28 revised full papers were carefully reviewed and selected from 104 submissions. The papers are organized in topical sections on post-quantum cryptology, key agreement protocols, side channel attacks, symmetric cryptology, hash functions, number theoretic cryptology, lightweight cryptology, signature protocols, and multiparty computation.